Sexual violence and American slavery: the making of a rape culture in the antebellum South - Eaves, Shannon (The University of North Carolina Press, 2024)
"It is impossible to separate histories of sexual violence and the enslavement of Black women in the antebellum South. Rape permeated the lives of all who existed in that system: Black and white, male and female, adult and child, enslaved and free. Shannon Eaves unflinchingly investigates how both enslaved people and their enslavers experienced the systematic rape and sexual exploitation of bondswomen and came to understand what this culture of sexualized violence meant for themselves and others. Eaves mines a wealth of primary sources including autobiographies, diaries, court records, and more to show that rape and other forms of sexual exploitation entangled slaves and slave owners in battles over power to protect oneself and one's community, power to avenge hurt and humiliation, and power to punish and eliminate future threats. By placing sexual violence at the center of the systems of power and culture, Eaves shows how the South's rape culture was revealed in enslaved people's and their enslavers' interactions with one another and with members of their respective communities"-- Provided by publisher